Adult attitudes towards Dene Yati/Zhatié: a community questionnaire - Coates, Alice (2025)
A comparison of language attitudes in adults from two Dene-speaking communities in Canada’s Northwest Territories describes attitudes which are broadly homogenous, with some variation dependent on demographics and beliefs regarding the language and language vitality. The results of the study show overall low attitudes among respondents in both communities, affected by the rating of the use of the language in workplaces and despite strongly positive attitudes in the affective dimension. Positive attitudes in an individual are associated with strength of Dene identity and proficiency in the language, with these conditions promoting one another. Concerns about language vitality are reflected in both communities’ focus on the importance of generational language transfer occurring in the home. The fact that the majority of survey respondents rate themselves as emergent speakers of the language may be indicative of low rates of language use, in turn contributing to concerns about vitality. However, the broad base of support for the language and language learning in the communities shows awareness of the situation and a keen understanding of the value of the language to cultural revitalization and its potential contribution to wellness amongst young learners. May 2025